On the margins of suicide: everyday horizons, turning points and trajectories of protection in peripheral young women - Orli Carvalho da Silva Filho; Joviana Quintes Avanci; Simone Gonçalves de Assis (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract: Suicidal behavior and non-suicidal self-harm in vulnerable groups and population minorities pose a challenge for suicidology, complicating the universality of suicide. The goal of this paper is to analyze the lives of young women from marginalized communities, considering their experiences with suicidality and their relational and violent horizons. Nine women who took part in the fifth wave of a cohort on mental health and violence (2005-2022) in São Gonçalo, Rio de Janeiro State, Brazil, were interviewed (2022) about the contexts that kept them from committing suicide despite significant emotional distress from childhood through youth. From theme-based content analysis, three categories stood out and may contribute to an intersectional, decolonial and socially relevant approach to preventing self-destructive behavior. In the first, views on self-inflicted violence, better explained by the cores concepts of "sin" and "illness" than by the general violence they experienced. In the second, indirect references to self-harm behavior, where it was recognized that the use of euphemisms reflects not only the taboo but also the silencing of and discrimination against minorities. In the third, layers of protection and turning points, where "spirituality", "occupation" and "motherhood" were interpreted as the main associations between factors of protection and resilience in the trajectories and daily lives of these young women. A closer look that acknowledges the humanity, rights and psychological distress of groups subjected to violence and discrimination not only enhances care and prevention of suicidal behavior but also deepens understanding of this human and universal phenomenon.